Bile acids are essential for porcine enteric calicivirus replication in association with down-regulation of signal transducer and activator of transcription 1 - Chang, Kyeong-Ok (National Academy of Sciences, 2004)
A porcine enteric calicivirus (PEC), strain Cowden in the family Caliciviridae (genus Sapovirus), can be propagated in a continuous cell line, LLC-PK cells, but only in the presence of an intestinal content fluid filtrate from gnotobiotic pigs. This cell culture system is presently the only in vitro model among caliciviruses that cause gastrointestinal disease, including members of the genera Sapovirus and Norovirus. We report here the identification of bile acids as active factors in intestinal content fluid essential for PEC growth. Bile acids that allowed PEC growth induced an increase in cAMP concentration in LLC-PK cells that was associated with down-regulation of IFN-mediated signal transducer and activator of transcription 1 phosphorylation, a key element in innate immunity. In addition, cAMP/protein kinase A pathway inhibitors, suramin, MDL12330A, or H89 suppressed bile acid-mediated PEC replication. We propose a mechanism for enteric calicivirus growth dependent on bile acids, ubiquitous molecules present in the intestine at the site of the virus replication that involves the protein kinase A cell-signaling pathway and a possible down-regulation of innate immunity.